The Comparison of Cost-Effectiveness Between Magnetic Resonance Spectroscopy and Provocative Discography in the Identification of Chronic Low Back Pain Surgery Candidates - Wilson L; Beall DP; Eastlack RK; Berven S; Lotz JC (ClinicoEconomics and Outcomes Research)
Leslie Wilson,1 Douglas P Beall,2 Robert Kenneth Eastlack,3 Sigurd Berven,4 Jeffrey C Lotz4 1Department of Pharmacy, UC San Francisco, San Francisco, CA, 94143, USA; 2Comprehensive Specialty Care, Edmond, OK, 73034, USA; 3Department of Orthopaedic Surgery, Scripps Clinic, La Jolla, CA, 92037, USA; 4Department of Orthopaedic Surgery, UC San Francisco, San Francisco, CA, 94143-0728, USACorrespondence: Leslie Wilson, Department of Pharmacy, UC San Francisco, San Francisco, CA, 94143, USA, Tel +1 415-990-1012, Email leslie.wilson@ucsf.eduBackground/Context: Chronic low back pain (CLBP) is a significant US healthcare burden with millions of lumbar spine procedures annually. Diagnostic tests are essential to guide treatment but provocative discography (PD), the most common diagnostic procedure, is without robust evidence of its value. A non-invasive alternative using Magnetic Resonance Spectroscopy (MRS) offers a potential solution.Context/Purpose: We assess cost-effectiveness of MRS with NOCISCAN diagnostic algorithm compared to PD for identifying lumbar discs requiring surgical intervention.Study Design/Setting: We conducted cost-effectiveness analysis using modelling.Patient Sample: We used data from a clinical study of 139 CLBP patients who met criteria for and received PD of lumbar spine and presented with an ODI score ≥ 40; comparing PD and MRS-based diagnostics.Outcome Measures: We considered diagnostic costs, adverse events, surgical costs and outcomes based on a 15-point improvement on the Oswestry Disability Index.Methods: Incremental cost-effectiveness ratios (ICERS) and probabilistic sensitivity analyses were determined. Some authors have consulted for Aclarion.Results: Mean total cost per PD patient was $59,711, and $57,998 for MRS, demonstrating $1712 cost savings per MRS diagnosed patient. Diagnostic costs ($1950 for PD; $1450 for MRS), saved $500 per MRS patient. PD incurred adverse event costs ($57,323) for 1% of patients, which MRS eliminated. MRS-based diagnosis showed 78% surgical success, whereas PD achieved 68%. MRS was the dominant diagnostic strategy, with better clinical outcomes and cost savings. Probabilistic sensitivity analysis confirmed MRS dominance and was cost-effective across a wide range of willingness-to-pay thresholds and across 2 different scenarios which vary base-case outcomes and surgical rates.Conclusion: This study demonstrates cost-effectiveness dominance of MRS with the Nociscan diagnostic algorithm over PD for identifying CLBP surgical candidates. MRS provides significant cost savings and leads to better surgical outcomes, making it a preferred choice for insurers and health systems.Plain Language Summary: Chronic low back pain (cLBP) is experienced by 20% of the US population. It is difficult to determine the best treatment, and many have unnecessary surgery. Discography is the currently available diagnostic but is invasive, of limited value and with serious adverse events. MRS+Nociscan, a new non-invasive diagnostic uses MR Spectroscopy and an algorithm to identify painful discs, is FDA registered. Our aim is to conduct a cost-effectiveness analysis (CEA) to compare the economic value of these two diagnostic procedures. Subjects were part of a multicenter study of 139 patients who received MR imaging and PD for chronic low back pain. The intervertebral disc MRS data post-processing was performed using the NOCISCAN-LS software algorithm. We developed a decision tree model comparing provocative discogram (PD) with an MRS+ Nociscan diagnostic algorithm using a health system perspective over 12-months. The primary endpoint was surgical ODI success or failure. Costs were from the Medicare Fee Schedule. We calculated in incremental cost-effectiveness ratio (ICER), in terms of the additional cost or savings per additional treatment success gained. The mean total PD group cost per patient was $59,711 and $57,998 in the MRS+Nociscan group demonstrating that MRS-based diagnosis saved $1712 per patient diagnosed. Clinical success with MRS-based diagnosis was 78%, and 68% with PD diagnosis. The cost-effectiveness demonstrated strong MRS-Nociscan dominance, meaning it was both cost saving and a better clinical success. The strong cost-effectiveness dominance for MRS+Nociscan diagnosis answers the budgetary questions for insurers and health systems considering adoption of this new diagnostic tool.Keywords: cost, cost-effectiveness, lumbar spine, diagnostics, outcomes, discography